Penyelesaian Masalah Transshipment pada Pendistribusian Tempe Menggunakan Metode Max-Min - Febriana, Febriana; Helmi, Helmi; Fran, Fransiskus (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2024)
Tempe is a daily food of Indonesian people that is famous for its high nutritional content. One of the home industries that produce tempe in Pontianak City is Pabrik Tempe Tuan Y. In distributing tempe, Pabrik Tempe Tuan Y  applies a transshipment system with two markets as transit points, where these two markets have different locations. This study aims to determine the solution to the tempe distribution problem and determine the minimum distribution cost that can be incurred by Pabrik Tempe Tuan Y. The problem in this study is a transshipment problem with mixed constraints, where the source and destination constraints consist not only of equation signs but also inequality signs. The Max-Min method is a method for solving transshipment problems with mixed constraints that can be used to obtain optimal solutions from solving all types of transshipment problems. The transshipment problem is organized in the form of a transportation table. The table is then solved using the Max-Min method. The results showed a decrease in total transportation costs from Rp 292,136.00 to Rp 260,193.00 with a cost difference of Rp 31,943.00.  Keywords: Transportation Problem, Transshipment Problem with Mixed Constraints, Max-Min Method.